Essays on stakeholder economy - ZHANG, Hanyu (Institutional Knowledge at Singapore Management University, 2023)
The dissertation consists of two chapters on stakeholder economy. It looks at how firms interact with the stakeholders, including not only investors, employees, customers, governments, but also the broader community and society at large, and examines how such interactions affect corporate behavior in China and the global setting. The first chapter studies how societal culture shapes firm behavior and growth by analyzing the trade-off of relying on trust in acquiring stakeholder resources, and testing with data on the number of historic Confucian schools surrounding a current firm’s location in China. Companies more exposed to Confucianism have greater social contributions and stakeholder protection, and more business courtesy expenses, patents, and trade credits, which match the five basic virtues of Confucianism: benevolence, righteousness, courteousness, wisdom, and trustworthiness. Our results cannot be explained by other cultural traits and are robust to using the distance to the prototypical Confucian academies in the Song Dynasty and the intensity of rivers in the local region as instrumental variables. The effects are likely to be transmitted via a firm’s interaction with market participants, politicians’ ideology, and board of directors. Stronger Confucianism is associated with greater profitability and growth. Our paper contributes to the literature by providing more granular evidence on how culture affects economic activities through firm-level channels, which have not been systematically explored in the literature. In the second chapter, we employ a novel firm-level dataset on monetized value of unpriced earnings losses due to climate-related transition risks to study the magnitudes, determinants and consequences of a firm’s carbon earnings risks across different scenarios based on national pledges to Paris Agreement targets and different time horizons. We find carbon earnings risks on average account for about 15 percent of a firm’s total earnings and are largely driven by unobservable industry- and firm-level heterogeneities. We also find that companies with greater carbon earnings risks tend to have more green innovations, discretionary accruals, and outsourced productions. We use the staggered introduction of country-level carbon tax and emission trading system, as well as state-level climate-related disasters as instrumental variables to address potential endogeneity issues. Our findings highlight the importance of accounting for transition risks in a firm’s financial statements. Our work complements the growing climate finance literature on the effect of climate risks on corporate policies by providing more comprehensive evidence on the motivation of corporate reaction, driven by material carbon earnings risks that are reflected on a firms financials.